2012
DOI: 10.1177/0892705712452739
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of SiO2, ZnO and nanoclay on mechanical and thermal properties of wood polymer nanocomposite

Abstract: Wood polymer composite (WPC) was prepared using solution-blended high-density polyethylene (HDPE), low-density polyethylene (LDPE), polypropylene (PP), poly(vinyl chloride) (PVC), wood flour (WF) and polyethylene-co-glycidyl methacrylate (PE-co-GMA). The effect of nanoclay, SiO 2 and ZnO addition on the properties of the composite was examined. The distribution of silicate layers, SiO 2 and ZnO nanopowder was studied by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The improvement in misc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 39 publications
1
25
0
2
Order By: Relevance
“…The FTIR spectra of the WF (Figure 5) show absorption bands originated from O-H stretching vibrations at 3435 cm À1 , -CH stretching vibrations at 2924 and 2855 cm À1 , C¼O stretching vibrations at 1736 cm À1 , -OH bending vibration at 1656 cm À1 , C-O stretching vibrations at 1112 and 1043 cm À1 , and C-H bending vibration at 1000-669 cm À1 (out of plane). Similar values for these absorption bands were found by Deka et al 33 The absorption band at 1656 cm À1 corresponds to the C¼C stretching of aromatic skeletal in lignin. 34 However, FTIR spectra of cured resins showed characteristic absorption bands in this region.…”
Section: Ftir Spectroscopysupporting
confidence: 87%
“…The FTIR spectra of the WF (Figure 5) show absorption bands originated from O-H stretching vibrations at 3435 cm À1 , -CH stretching vibrations at 2924 and 2855 cm À1 , C¼O stretching vibrations at 1736 cm À1 , -OH bending vibration at 1656 cm À1 , C-O stretching vibrations at 1112 and 1043 cm À1 , and C-H bending vibration at 1000-669 cm À1 (out of plane). Similar values for these absorption bands were found by Deka et al 33 The absorption band at 1656 cm À1 corresponds to the C¼C stretching of aromatic skeletal in lignin. 34 However, FTIR spectra of cured resins showed characteristic absorption bands in this region.…”
Section: Ftir Spectroscopysupporting
confidence: 87%
“…These results demonstrated that the ZnO NPs had an enhancing effect on the mechanical properties of wood-fiber-polymer composites. Figure 9 f displays the comparison of the mechanical properties of the PZW composites with those of other peer biomass materials, showing that the properties of the PZW composites were better than those of the other materials [ 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wood plastic nanocomposites are usually produced by extrusion, 2,25 28 injection 9,29 32 or compression molding. 17,22 24,33 35 One of the challenges in nanocomposite manufacturing is achieving homogeneous dispersion of the nanofiller throughout the composite material. The appropriate method for the compounding, the proper choice of the extruder type and its screw design may improve the degree of nanofiller dispersion in the composite significantly, which, in turn, improves the quality of the final product.…”
Section: Wpc Nanocomposite Manufacturingmentioning
confidence: 99%